Naturalized Escherichia coli in Wastewater and the Co-evolution of Bacterial Resistance to Water Treatment and Antibiotics - Yu, Daniel; Ryu, Kanghee; Zhi, Shuai; Otto, Simon J. G.; Neumann, Norman F. (Frontiers in Microbiology, 2022)
Antibiotic resistance represents one of the most pressing concerns facing public health today. While the current antibiotic resistance crisis is generally understood to have been primarily driven by the anthropogenic overuse of antibiotics, recent efforts have revealed several important environmental dimensions underlying this public health issue. Reflecting this, antibiotic resistant (AR) microbes, AR genes, and antibiotics themselves have been found to be widespread in natural environments, suggesting the ancient origins of the phenomenon of antibiotic resistance. The irony that rests in microbes possessing ancient solutions to the modern problem of the use of antibiotics as therapeutics serves to illustrate the power that natural selection has on microbes for overcoming threats to their existence. These powerful evolutionary processes drive the emergence of new microbial entities, even within engineered environments designed to destroy them. Such an example can be seen in the recent discovery of naturalized populations of E. coli found in sewage and wastewater treatment plants around the world. Remarkably, these strains carry a plethora of stress-resistance genes to overcome the very water treatment processes designed to destroy them (i.e., chlorination, heat, UV light advanced oxidation), facilitating their exploitation of the wastewater environment as a primary niche for survival. These naturalized populations also possess various antibiotic resistance genes, which may further promote survival in the wastewater matrix. Worryingly, evidence suggests that these naturalized strains may be playing a fundamental role in the evolutionary emergence of water treatment-resistant extraintestinal pathogenic E. coli (ExPEC). Indeed, phenotypic resistance to water treatment has already been demonstrated in ExPEC populations and appears to be associated with the presence of various shared genetic elements with naturalized wastewater E. coli. Concerningly, these data suggest that microbes may have solved the two most important public health interventions that are fundamental for the control of infectious disease in modern society – antibiotic therapy and water treatment.